Application of Acupressure in Reducing Pruritus Scale in Hemodialysis Patients - Panma, Yuanita; Yetti, Krisna; Sukmarini, Lestari (KnE Life Sciences, 2021)
Pruritus is a common problem in patients with chronic kidney disease who undergo dialysis. It is characterized by an uncomfortable sensation that leads to scratching. Acupressure is a complementary method used to manage various symptoms and health problems, including pruritus. This study aims to identify the effect of acupressure at the LI-11 point in reducing pruritus in a hemodialysis patient. This study used pre-experimental research with pre- and post-test without control. This study occurs in a hemodialysis unit in Central Jakarta, Indonesia. The sample was comprised of 19 respondents in the hemodialysis unit who met the inclusion criteria and completed the study. Respondents received acupressure in the LI-11 point two times per week for four weeks for a total of eight sessions. Data were collected using individual characteristics questionnaire, pruritus characteristics, and Visual Analog Scale (VAS) for pruritus. The data analysis used was a dependent t-test. The majority of respondents were male with duration of hemodialysis 5 hours, mean of age 53 years, mean of length of HD is 53 months, mean of Hb level is 9.67 gr/dl, mean of urea level is 117.05 mg/dl, mean of creatinine is 10.26 mg/dl. The results indicate that acupressure has a significant effect in reducing of pruritus scale (p-value 0,000). This study recommends nurses to be able to use acupressure therapy to reduce the scale of pruritus experienced by hemodialysis patients. Keywords: acupressure, pruritus, hemodialysis